Accounting: Texts and Cases - Anthony Robert N (Mc Graw Hill Technoloy Education, 2010)
Accounting: Text & Cases is a product of lifelong dedication to the discipline of accounting. Covering both financial and managerial accounting as well as broader managerial issues, the book incorporates a breadth of experience that is sure to enrich your course and your students. The approximately 109 cases that make up most of the end of chapter material are combination of classic Harvard style cases and extended problems, with 12 complete new cases added to the 13th edition.